2016
DOI: 10.3122/jabfm.2016.01.150205
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders' Recommendations to Improve Patient-centered "LGBTQ" Primary Care in Rural and Multicultural Practices

Abstract: Purpose: Individuals among gender/sexual minorities share experiences of stigma and discrimination, yet have distinctive health care needs influenced by ethnic/racial minority and rural realities.Methods: We collected qualitative data from lesbian/gay/bisexual/transgender (LGBT) and queer persons across the largely rural, multicultural state of New Mexico, particularly those from understudied ethnic groups, regarding factors facilitating or impeding patient-centered primary care. The themes identified formed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 10 publications
0
26
0
9
Order By: Relevance
“…Perceived stigma in clinical settings may discourage MSM from accessing needed health care services to advance sexual health and overall well-being (Clift & Kirby, 2012;Eaton et al, 2015;Sabin, Riskind, & Nosek, 2015). Experiences may be exacerbated in socially conservative and rural areas where LGBT populations have less access to quality, LGBT-sensitive care (Kano, Silva-Bañuelos, Sturm, & Willging, 2016;Rosenkrantz, Black, Abreu, Aleshire, & Fallin-Bennett, 2016;Whitehead et al, 2016). As such, MSM are required to travel farther to find LGBT-affirming providers within Oklahoma and neighboring states who may be willing to see LGBT patients and who would also be willing to prescribe PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived stigma in clinical settings may discourage MSM from accessing needed health care services to advance sexual health and overall well-being (Clift & Kirby, 2012;Eaton et al, 2015;Sabin, Riskind, & Nosek, 2015). Experiences may be exacerbated in socially conservative and rural areas where LGBT populations have less access to quality, LGBT-sensitive care (Kano, Silva-Bañuelos, Sturm, & Willging, 2016;Rosenkrantz, Black, Abreu, Aleshire, & Fallin-Bennett, 2016;Whitehead et al, 2016). As such, MSM are required to travel farther to find LGBT-affirming providers within Oklahoma and neighboring states who may be willing to see LGBT patients and who would also be willing to prescribe PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…For rural LGBTQ patients, long‐term relationships with providers can be a mechanism for mediating documented concerns related to anticipated stigma and “outing” oneself to multiple medical providers . With its wide scope and focus on prevention, primary care is uniquely poised to address concerns of vulnerable and minority groups, such as rural LGBTQ individuals …”
mentioning
confidence: 99%
“…34 With its wide scope and focus on prevention, primary care is uniquely poised to address concerns of vulnerable and minority groups, such as rural LGBTQ individuals. 35 Despite the advantageous position of primary care providers to address the health concerns of rural LGBTQ individuals, little is known about their actual knowledge or experiences with this subpopulation. 21 A recent review of literature concerning the health of rural LGBTQ individuals 21 found only 3 studies assessing the educational preparedness of rural health care providers.…”
mentioning
confidence: 99%
“…In addition, in this issue Kano et al 16 single out the lesbian/gay/bisexual/trans/queer population and demonstrates the impact of moving from a one-size-fits-all model of primary care to a population-driven design meant to be accessed by specific segments of the community. Thinking through the needs of specific populations not only achieves better quality care but engenders a patient's perception of better service.…”
mentioning
confidence: 99%